Analysis of Delay Management Supervision by Air Transport Inspectors at Soekarno Hatta International Airport - Qois Alqoroni Masyhuda; Nur Makkie Perdana Kusuma (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The Air Transport Inspector carries out supervision according to objects and events directly in the field. Supervision carried out by the Air Transport Inspector is very important in order to maintain security and safety during operations at the airport. The purpose of this study was to determine the effect of supervision and the results of monitoring delays by the Air Transport Inspector at Soekarno-Hatta International Airport. This study uses a qualitative method. Data collection was carried out at the Regional Airport Authority Office. Data was obtained from observations, interviews and documentation. Primary data sources were obtained from interviews with 5 (five) informants consisting of the Head of the Air Transport Section and 4 (four) Air Transport Inspectors. Secondary data was obtained from Delay Management SOP data, Ministerial Regulations, Air Transport Inspector Supervision Report Data and supervision documentation. The results showed that there were flight delays on Batik Air caused by delays at the previous airport, VIP movements, and technical service. In this incident it has been handled properly and compensation has been given based on the categories listed in PM 89 of 2015. The important role of the Air Transport Inspector is very influential in monitoring delays. Despite the shortage of personnel, the late information received by the Air Transport Inspector, the Air Transport Inspector has carried out scheduled and organized inspections. Even though it is in accordance with the SOP, the Inspector's supervision needs to be improved again so that in the future it will be more efficient and effective.